KRITIK SALIM AL-JAbI ATAS HERMENEUTIKA MUHAMMAD SYAHRUR - Syamsul Wathani (el-'Umdah, 2018)
Criticism in interpretation studies shows a new phase of the interpretation of the Qur’an in contemporary academic studies of the Qur’an. Muhammad Syahrur is a fgure who became the object of criticism for some of his renewed ideas in contemporary studies of the Qur’an which are packaged in hermeneutics. Mahir al-Munanjad passed his book al-iskâ liyat Qirâ ah and Salim al-Jabi, al-Qirâ ‘at al-Mu’â shirat. This article focuses on Al-Jabi thinking with analysis on critical points. Al-Jabi made anBacademic criticism of Syahrur’s study, especially in the pattern of the approach used by Syahrur. Al-Jabi offers textual-contextual criticisms of the Shahrur approach patterned on language and thematic-historical analysis, which are often not in the context of the verses of the Qur’an.